The reality of digital transformation in the tax sector in Algeria (Strategy and Challenges) - Rezigat, Boubaker; Zergoune, Mohamed; Bouakaz, Youcef (International journal of economic perspectives, 2025)
This study aimed to provide a comprehensive analysis of the reality of digital transformation in Algeria by examining the strategy adopted by the Algerian legislator for the digital transformation of the tax sector, in addition to addressing the most important challenges facing the modernization of the tax sector in Algeria. The study concluded that the most important strategies for digital transformation in Algeria are (the need to create a favorable environment for digital transformation, developing e-governance, Accelerate the process of digitizing the administration, creating a favorable environment for the development of the digital economy and promoting digital citizenship.) Digital transformation in the tax sector also faces challenges, the most important of which are (technical and infrastructural challenges, Legal and organizational challenges, Cultural and societal challenges, Tax administration challenges related to the digital economy and taxpayer challenges).